Transgender and Gender-Nonconforming Populations Experience Unique Challenges in Health Information Environment Developed for Heteronormative Audience / Tenny, C. S., Surkan, K. J., Gerido, L. H., & Betts-Green, D. (2021). A crisis of erasure: Transgender and gender-nonconforming populations navigating breast cancer health information. The International Journal of Information, Diversity, & Inclusion, 5(4), 132–149. https://doi.org/10.33137/ijidi.v5i4.37406 - Shen, Lisa (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objective – To understand the lived experiences of transgender and gender-nonconforming populations in seeking health information about breast cancer.Design – Thematic literature review.Setting – Four English-language databases featuring clinical, patient engagement, and library and information sciences (LIS) research.Subjects – Twenty-one published articles.Methods – The researchers chose three concepts (trans, LGBTQ+, and breast cancer), identified related terms for each, and used these terms to conduct literature searches in four databases: PubMed, Web of Science, Library Literature & Information Science Full Text, and Library, Information, Science & Technology Abstracts. Search results were reviewed for relevance to the research objective. The researchers applied grounded theory to analyze the 21 selected articles through open, axial, and selective (thematic) coding. The qualitative research software NVivo was used to perform thematic analysis of each article, and a shared codebook was developed to ensure saturation of axial themes and consistency of coding amongst researchers.Main Results – Three overarching themes emerged from selective coding that exemplify experiences of transgender and gender-nonconforming persons seeking health information about breast cancer: access, erasure, and quality. Compared to their cisgender peers, these historically marginalized populations and their caregivers experience more difficulty accessing the already limited breast cancer information, healthcare, and support services suited to their needs. In particular, transgender and gender-nonconforming patients are often burdened with choosing between receiving health information and care designed for heteronormative persons and risking self-disclosure and possible discrimination by culturally incompetent health professionals.Conclusion – The researchers noted the alarmingly limited resources available for gender-nonconforming patients seeking information and support for health matters other than mental health or sexually transmitted diseases. The researchers also called for increased efforts by LIS curriculums and professionals to study and understand the needs of transgender and gender-nonconforming patrons, and to improve the quality and quantity of information resources specifically dedicated to these unique populations.